A Study on the Design of a Variable Power Electromagnetic Brake for Industrial Applications - Ye-Ji Park; Jae-Kwang Lee; Ki-Doek Lee; Dong-Hoon Jung (Machines)
This paper discusses a permanent-magnet electromagnetic brake for the semiconductor process of hollow integrated modules. This permanent-magnet electromagnetic brake is characterized by permanent magnets arranged at the bottom of the stator and coils positioned in the middle portion of the stator. The attractive force is generated by the magnetic energy from the permanent magnet, and to counteract the holding force, a current must be applied to the coils. In the case of a permanent-magnet electromagnetic brake, the maximum holding force that can be generated is fixed by the permanent magnet inserted at the bottom, and even if the load conditions vary, the holding force cannot be altered. This study investigated a method to secure an additional holding force by inducing iron losses at the moment when the holding force is required through improvements in the structure of both the stator and rotor of a permanent-magnet electromagnetic brake. To validate the feasibility of this study, prototypes of permanent-magnet brakes were fabricated, and dynamometer tests were conducted.